Antimony in rutile as a pathfinder for orogenic gold deposits - Agangi, Andrea; Reddy, Steven; Plavsa, D.; Fougerouse, Denis; Clark, Christopher; Roberts, M.; Johnson, Tim (Elsevier Science BV, 2019)
In our study we explore the applicability of rutile as a pathfinder for orogenic gold deposits, which are an important source of this metal worldwide. We analysed rutile associated with orogenic Au deposits from three different Precambrian terranes, the Capricorn Orogen, the Barberton Greenstone Belt and the Ashanti Belt, all of which formed under greenschist conditions and share similarities in the style of mineralisation. Microtextural evidence from scanning electron microscopy and electron back-scatter diffraction indicates that rutile formed during the main deformation and alteration stage in these rocks, and is therefore related to mineralisation. We used electron microprobe and laser ablation ICP-MS to investigate the trace element compositions of rutile and we compared our results to other gold deposits. We find that hydrothermal rutile from gold deposits contains certain trace element characteristics, in particular high Sb concentrations (up to ~1500 ppm in Au deposits of the Capricorn Orogen), that are distinct from rutile from non-mineralised rocks of various petrogenetic origin. Other elements, such as W and Sn, are found to be more enriched in rutile from other rock types, namely felsic magmatic rocks and hydrothermal veins, and are therefore not diagnostic of Au mineralisation in this type of deposits. We also find that the presence of sub-µm-scale inclusions – in particular Zr-(Si, Th)-bearing phases, sulfide minerals and native Au – can severely affect analyses of this type of rutile and compromise the applicability of Zr-in-rutile geothermometry.